1999
DOI: 10.1046/j.1365-2761.1999.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental host range and histopathology of white spot syndrome virus (WSSV) infection in shrimp, prawns, crabs and lobsters from India

Abstract: Experimental studies were conducted by injecting or feeding white spot syndrome virus (WSSV) derived from infected shrimp, Penaeus monodon (Fabricius), collected from the south‐east coast of India, to five species of shrimp, two species of freshwater prawns, four species of crabs and three species of lobsters. All species examined were susceptible to the virus. Experimental infections in the shrimp had the same clinical symptoms and histopathological characteristics as in naturally infected P. monodon. A cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
97
1
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 11 publications
8
97
1
5
Order By: Relevance
“…Evidence of histopathological manifestations in the target tissues is one of the criteria used in the diagnosis of WSSV infection (Lightner 1996;Wang et al 1997). During our investigation on the histopathology of the WSSV infection, we have noticed obvious histological changes characteristic of WSSV in the cuticular epidermis of eyestalk and pleopod (Rajendran et al , 1999, which is in agreement with the observation of Chang et al 1996 andLo et al 1997. Epithelial cells of the eyestalk and pleopod are the preferred tissues of WSSV, and the initial sites of viral infection (Chang et al 1996;Lo et al 1997).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Evidence of histopathological manifestations in the target tissues is one of the criteria used in the diagnosis of WSSV infection (Lightner 1996;Wang et al 1997). During our investigation on the histopathology of the WSSV infection, we have noticed obvious histological changes characteristic of WSSV in the cuticular epidermis of eyestalk and pleopod (Rajendran et al , 1999, which is in agreement with the observation of Chang et al 1996 andLo et al 1997. Epithelial cells of the eyestalk and pleopod are the preferred tissues of WSSV, and the initial sites of viral infection (Chang et al 1996;Lo et al 1997).…”
Section: Introductionsupporting
confidence: 88%
“…Histopathological evidence has shown that this virus replicates in tissues of ectodermal and mesodermal origin only (Chou et al 1995;Lightner 1996;Karunasagar et al 1997;Mohan et al 1997;Rajendran et al 1999, Yoganandhan et al 2003Vijayan et al 2003). Evidence of histopathological manifestations in the target tissues is one of the criteria used in the diagnosis of WSSV infection (Lightner 1996;Wang et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Since its advent in 1992, WSV has greatly affected the shrimp farming industry (Mohan et al, 1997). This pathogen has tropism for organs of mesodermal and ectodermal origin (Wongteerasupaya et al,1995(Wongteerasupaya et al, , 1996Chang et al, 1996;Flegel et al, 1997;Rajendran et al, 1999;Wang et al, 1999;Vijayan et al, 2003;Yoganandhan et al, 2003). Evidence of histopathological manifestations in the target tissues is one of the criteria used in the diagnosis of WSV infection (Lightner, 1996;Wang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenicity of WSSV has also been investigated in the spiny lobster species P. versicolor, P. penicillatus, P. ornatus, P. longipes, P. homarus and P. polyphagous (Chang et al 1998, Rajendran et al 1999, Musthaq et al 2006. Chang et al (1998) reported that lobsters fed WSSV-contaminated feed did not succumb (although WSSV was detected within their tissues), while Rajendran et al (1999) provided some evidence that WSSV infection via feeding and ingestion could result in mortalities of P. polyphagous and P. ornatus. However, in a follow-up study by Musthaq et al (2006), P. homarus and P. ornatus fed WSSV-contaminated feed did not die, while those that were injected with WSSV did.…”
Section: Discussionmentioning
confidence: 99%